Tingkat Kecemasan dan Faktor Risikonya pada Mahasiswa Kedokteran Universitas Pattimura Ambon Tahun 2020/2021 selama Pembelajaran Daring di Masa Pandemi COVID-19 - Bill E. Nanere; Sherly Yakobus; Alessandra F. Saija (Lembaga Pengembangan Kinerja Dosen, 2025)
Anxiety is a common phenomenon that is a universal cause of poor academic performance among students worldwide. Anxiety can also have an impact on student learning. Bold learning carried out during the Covid-19 pandemic caused anxiety or pressure for some students which could result in confusion, decrease the ability to direct attention, decrease memory, and interfere with students' concentration. The purpose of this study was to describe the level of anxiety in the pre-clinical group of FK Unpatti, age, gender, place of residence, consuming alcoholic beverages. This research is a descriptive study using a cross-sectional approach which was conducted in September 2021. The number of respondents collected was 535 respondents based on total sampling. The analysis used is univariate analysis. The data obtained using the Hamilton Rating Scale for Anxiety (HRS-A) questionnaire. The results of this study were obtained mostly in unhurried conditions based on the batch of 2020 (32.8%), class of 2019 (22.5%), class of 2018 (26.2%) and class of 2017 (18.5%). Based on age, namely at 17 years (1.2%), at 18 years (37.9%), at 19-20 years (28.3%), at 21 years (25.1%) and at 22 years ( 7.5%). Based on gender male (26.9%) and female (73.1%). Based on the place of residence with parents (50.8%) and not with parents (49.2%). Based on consuming alcoholic beverages (2.8%) and not consuming alcoholic beverages (97.2%). Research shows that there are variations in the level of anxiety in pre-clinical students of FK Unpatti who take courageous learning.